APLIKASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERUMAHAN DENGAN METODE FUZZY TOPSIS MENGGUNAKAN PHP - Sushanty Saleh (Jurnal Informatika, 2012)
Belfast city region has an area of ​​197.22 km2 with a total population of 881 801 inhabitants (census 2010), with jiwa/km2 4471,154 population density and population growth rate of 1.79% per year (lampung.bps.go.id). Increasing the number of residents in the city of Bandar Lampung is not followed by increments of land giving rise to problems, especially for housing residents. Topsis Fuzzy methods used to find a recommended ranking of housing alternatives for consumers in the housing selection decisions. Both of the test results and calculations with the Excel program, the alternative selected / recommended by Topsis seen from the low price, land area and building area is quite, and facilities using methods FMADM terpenuhi.Perhitungan Topsis compliance calculations obtained by the application program used for all criteria are calculated on TOPSIS after testing the application program. Keywords: Fuzzy, Topsis, Housing